Consignes aux auteurs Presentation des articles - Dhatt, Gouri (European Journal of Computational Mechanics, 1992)
The instructions put together below fall into three categories. The editor of the review would be grateful to authors for respecting these indications. At times, the length of this summary may attain a dozen lines. It is to be written in size 9 italic Times. An abstract in French will be joined.